FACTORS RELATED TO NURSE COMPLIANCE IN APPLYING THE CATETER INSTALLATION STANDARD - Mohamad Judha; Ayu Silviana Rulis (Universitas Respati Yogyakarta, 2020)
Background: Urethral catheter placement is a form of nursing care performed by nurses, a standard for catheter placement is required. Urinary tract infections often occur around 40% of all hospital infections each year. In addition, from some researchers 80% of urinary tract infections occur due to the use of catheterization instruments, because almost 10% of all hospitalized patients, at Bantul Hospital in 2017 There are 21% of patients are infected with urinary tract. Nurse compliance uses standards based on various factors. Objective: To determine the factors associated with the participation of nurses in the implementation of the standard installation of urethral catheters in the inpatient room of Bantul Hospital. Methods: Descriptive analytic research by discussing cross sectional study. The sample used was total sampling with a sample of 43 nurses according to inclusion criteria. Data collection tools using questionnaires and observation sheets. Chi Square data analysis with α <0.05. Results: The gender of female respondents was 76.7%. Age of respondents received 18-40 years 76.7%. The level of knowledge of respondents in the good category is 65.1%. The attitude of respondents in the positive category was 83.7%. The working period of respondents <5 years 51.2%. There is a significant relationship to age with the implementation of the standard implementation of urethral catheters, (P = 0.003 with an OR value of 2.54). There is a significant relationship between knowledge and the implementation of standart urethral catheter placement (P = 0,000 with an OR value of 19.50). There is a significant relationship between attitude with the agreement on the implementation of the standard urethral catheter installation (P = 0.007 with an OR value of 0.361). There is a significant relationship between work period and the implementation of the standard implementation of urethral catheters (P = 0,000 with an OR value of 20.40). Conclusion: There is a significant relationship between age, knowledge, attitudes, and years of service to the approval of nurses in the implementation of the standard installation of urethral catheters in care in Bantul Hospital